Genetic relationship and identification of Dioscorea polystachya cultivars accessed by ISAP and SCAR markers - Peng, Bin; Zhang, Yanmei; Sun, Xiaoqin; Li, Mimi; Xue, Jiayu; Hang, Yueyu (Archives of Biological Sciences, 2017)
A survey of intron sequence amplified polymorphism (ISAP) in conjunction with sequence characterized amplified region (SCAR) was carried out to examine the genetic relationships among 14 Dioscorea polystachya cultivars and identify the most popular cultivar ‘Tiegun’. Our results revealed that there is a high level of polymorphism among these cultivars. Furthermore, in this study, ISAP markers were consistent with the morphological characters of Dioscorea polystachya cultivars and previous hypotheses on the classification of these cultivars into 2 groups via leaf and tuber shapes have been confirmed. Based on morphological characters and molecular data, we show for the first time that D. doryphora might be a single species and another progenitor of these cultivars. An ISAP fragment specific to the ‘Tiegun’ cultivar was converted into a SCAR marker. This marker could be used to discriminate the ‘Tiegun’ cultivar from the other 13 cultivars. Overall, the results of our study provide the foundations for subsequent breeding programs or conservation actions. https://doi.org/10.2298/ABS150717098P Received: July 17, 2015; Revised: September 18, 2015; Accepted: September 20, 2015; Published online: October 17, 2016 How to cite this article: Peng B, Zhang Y, Sun X, Li M, Xue J, Hang Y. Genetic relationship and identification of Dioscorea polystachya cultivars accessed by ISAP and SCAR markers. Arch Biol Sci. 2017;69(2):277-84.